The Strategy of New Product Introduction in Durable Goods with Secondary Market: Application of the Optimization Method to Supply Chain Problem - Pei Zhao; Zhongkai Xiong (Journal of Applied Mathematics)
The aim of this paper is to address how the secondary market affects the strategy of the manufacturer’s new product introduction by using the optimization method. To do so, we develop a two-period model in which a monopolistic manufacturer sells its new durable products directly to end consumers in both periods, while an entrant operates a reverse channel selling used products in the secondary market. We assume that the manufacturer launches a higher quality product in the second period for the technological innovation. We find that the secondary market can actually increase the manufacturer’s profitability and drives the new product introduction in the second period. We also derive the effect of the durability and the degree of quality improvement on the pricing of supply chain partners.